Criação de cidades possíveis: a montagem de Letícia Lampert em Random City - Cavalcante, Beatriz Rabelo (2024)
Amidst the scenario of intense image production, this research seeks to understand how the work Random City (2017), by Brazilian visual artist Letícia Lampert, allows a shift in the perspective of cities. In her work, she creates new landscapes by assembling photographs taken in different countries she visited, practicing an action of cutting, organizing, assembling and reassembling the images. Her landscapes carry pluralities, contrasts and the details of the everyday life. While many photographs produced today lack meaning and magic, Lampert tries to move against this movement, producing something that seems to burn in the image and leave the audience thinking. In this dissertation, a dialogue with text is carried out with authors such as Barthes (2017), Peixoto (1991) and Fontcuberta (2016). For Peixoto (1991), for example, everything is extremely obvious. Fontcuberta (2016) postulates that we live in a period marked by excess and that people are drowning in information. Thus, to understand how Lampert's work goes against the current of the movement of empty images, we critically reflect on the topic by dialoging with theorists who turn their gaze to art, photography and communication, such as Certeau (2007), Melendi ( 2017), Didi-Huberman (2018), Manguel (2001), Sontag (2004), Berger (2017) and Lampert herself (2017). The research, initially guided by Osmar Gonçalves dos Reis Filho (in memoriam), was inspired by Aby Warburg's Atlas Mnemosyne (2010), observing associative relationships in panels created from links with artists and photographers such as David Hockney and Giselle Beiguelman. Therefore, this research focuses on the message that the images evoke and the narratives they have to share. In the end, original boards were produced, with an assembly movement inspired by Letícia Lampert's creation process. It is clear, in this act of creating, that there are glimpses of the past in the present, and that the images invite us to wander and imagine about the lives of those who built and occupied urban spaces.